2021
DOI: 10.3390/vaccines9070789
|View full text |Cite
|
Sign up to set email alerts
|

Urban and Rural Disparities in Pneumococcal Carriage and Resistance in Jordanian Children, 2015–2019

Abstract: Background: A pneumococcal carriage surveillance study took place examining Jordanian children in urban and rural areas in the period 2015–2019. Objectives: To determine urban and rural differences in pneumococcal carriage rate, resistance, and serotypes among healthy Jordanian children from Amman (urban) and eastern Madaba (rural). Methods: Nasopharyngeal swabs (NP) were taken from 682 children aged 1 to 163 months. Pneumococcal identification, serotyping, and resistance were performed according to standard m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
(42 reference statements)
1
1
0
Order By: Relevance
“…A higher penicillin resistance (meningitis breakpoint) was found in the current study (96.5%), and it was slightly higher than that reported in the previous study [29]. This finding was in line with recently reported data from Jordan (94.4-95.8%) and Iran (95.3%) [12,42,43]. On other hand, the rate was higher than that found in GCC [44].…”
Section: Discussionsupporting
confidence: 90%
“…A higher penicillin resistance (meningitis breakpoint) was found in the current study (96.5%), and it was slightly higher than that reported in the previous study [29]. This finding was in line with recently reported data from Jordan (94.4-95.8%) and Iran (95.3%) [12,42,43]. On other hand, the rate was higher than that found in GCC [44].…”
Section: Discussionsupporting
confidence: 90%
“…According to the division of statistics of the Ministry of Health of Jordan, the total population count estimated in 2021 was 10,262,521, with an average family size of 6.1 members. This average of family members may attribute to the high carriage rate, in addition to other factors like low income, smoking among family members, history of sicknesses, immune deficiency, viral infections and history of antibiotic consumption [3,7,23,24]. In this study, the average number of siblings per household found was 3.7.…”
Section: Discussionmentioning
confidence: 53%